Examining Teachers' Perspectives on School Principals' Digital Leadership Roles and Technology Capabilities during the COVID-19 Pandemic - Karakose, Turgut; Polat, Hakan; Papadakis, Stamatios (Mdpi, 2021)
The current study investigates the perspectives and experiences of teachers regarding their school principal's digital leadership roles and technology capabilities during the COVID-19 pandemic. The research was conducted using a case study-based qualitative approach, and with a study group consisting of 89 teachers holding a Master's degree. Maximum diversity sampling, one of the purposive sampling methods, was preferred in the determination of the study group, and the data obtained from the research were analyzed through content analysis. The five main themes determined based on the perceptions and experiences of the participants are listed as: Digital technology usage, support for the digital transformation, support for technology-based professional development, support for digital learning culture, and digital leadership skills. The results of the research revealed that the level of use of digital technologies by school principals during the COVID-19 pandemic was perceived as adequate by teachers. In addition, it was determined that school principals support digital transformation and technology-based professional development in schools. Furthermore, within the scope of the research, it was determined that school principals contribute to the construction of a digital learning culture in schools. The results of the study revealed that school principals' digital leadership skills were clustered under three categories: technology use, managerial skills, and individual skills. As a result, in order to realize digital transformation within the context of K-12 education, school principals must first demonstrate their digital leadership and actively support the establishment of a digital learning culture in their schools.
Keywords: COVID-19; pandemic; digital leadership; technology capabilities; school principal; teachers; K-12 education